2012
DOI: 10.1590/s1413-41522012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Emprego do carvão ativado para remoção de atrazina em água de abastecimento público

Abstract: ResumoA atrazina é um dos herbicidas mais utilizados no mundo, sendo encontrada em águas superficiais e subterrâneas. Pertence à classe das s-triazinas, possui potencial carcinogênico e apresenta toxicidade como disruptor endócrino. A reconhecida limitação dos processos de tratamento de água, os quais empregam a coagulação química na remoção da atrazina e os efeitos na saúde, motivou este trabalho, considerando a adsorção em carvão ativado como tecnologia alternativa. O estudo experimental consistiu na caracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…This result was consistent with the IEC data of smectite clay minerals found in the literature, which show for the Brazilian smectite clays IEC values ranging from 22 to 151 meq/100 g of clay [9,10]. The variation in the IEC of the same clay mineral is also related to the degree of impurity; the higher it is, the lower the IEC [10,11]. From the X-ray diffractograms presented in Fig.…”
Section: Resultssupporting
confidence: 90%
“…This result was consistent with the IEC data of smectite clay minerals found in the literature, which show for the Brazilian smectite clays IEC values ranging from 22 to 151 meq/100 g of clay [9,10]. The variation in the IEC of the same clay mineral is also related to the degree of impurity; the higher it is, the lower the IEC [10,11]. From the X-ray diffractograms presented in Fig.…”
Section: Resultssupporting
confidence: 90%
“…When ATZ was present in ultrapure water, 35% of it was removed by the PSAC, and when present in the natural water sample was 25%, indicating that there is, undoubtedly, competition between other natural compounds present in the sample for PSAC active sites. However, it should be noted that the adsorbent mass used in this evaluation was very small and that larger masses of carbon could certainly remove all of the ATZ from the medium, as may already be observed from Table 2 data for PSAC masses equal to or greater than 0.0075 g. Coelho et al (2012), also described competition between ATZ and organic matter in adsorption studies using pulverized coconut shell activated carbon. They observed that the Adsorption Capacity Constant (Kf) value, in effluent water, suffered a reduction of 29%, demonstrating interference from other adsorbates in the TOC/ATZ relation.…”
Section: Psac Application In Natural Water Samplementioning
confidence: 61%
“…For comparison, iodine numbers for commercial PAC used to treat textile effluents are presented in Table 2. The iodine number for the PAC used in this work was considered high compared to those used by Kadirvelu et al (2000) and Coelho, Vazzoler and Leal (2012), and similar to those used by Al-Degs et al (2000) and Bestani et al (2008). The relatively high iodine number indicated that the PAC had a high number of micropores and a large surface area, since the adsorption of 1 mg of iodine corresponds to 1 m 2 of internal surface of the activated carbon (EL-HENDAWY; SAMRA; GIRGS, 2001).…”
Section: Iodine Numbermentioning
confidence: 62%